How content attributes of short video influence online purchase intention: the mediating role of perceived value - Fan, Wenjing; Osman, Syuhaily; Zainudin, Norzalina; Pinyi, Yao (Innovative Information Science and Technology Research Group, 2024)
In today’s digital landscape, short videos have become a dominant form of visual communication, captivating millions on social media and platforms like “TikTok.” As the short video sector flourishes, increasing businesses are turning to these platforms for marketing purposes. Despite this trend, there’s a noticeable gap in comprehensive understanding and research on the elements that drive consumer purchases through short video platforms. A survey exploring the impact of short video content attributes on consumer buying intentions was conducted to address this problem. The survey received input from 342 Chinese users of short video platforms. SEM was run to analyse data. The results of this study have shown that consumers tend to have both a better understanding and a more favourable impression of the product after watching clear and informative short videos. Additionally, the impact of clarity, practicality, and promotional prices on purchasing intentions is indirectly affected by the lens of the perceived value. The research offers insights into short video marketing and purchasing behaviour by providing valuable information regarding the Chinese market, but results may not apply elsewhere due to cultural and market differences. It is essential to explore in the next stage if the obtained outcomes are applicable to different cultures. Moreover, the study is based on self-reported data that can be influenced by social desirability bias and memory bias. Further studies might equip themselves with behavioral data, such as real purchase records, to complement the information from subjects to make up for the constraints of such self-reporting.